2019
DOI: 10.3389/fmicb.2019.00372
|View full text |Cite
|
Sign up to set email alerts
|

Sunagoke Moss (Racomitrium japonicum) Used for Greening Roofs Is Severely Damaged by Sclerotium delphinii and Protected by a Putative Bacillus amyloliquefaciens Isolate

Abstract: Mosses are ecologically important plants also used for greening, gardening, and decorative purposes. Knowledge of the microbial flora associated with mosses is expected to be important for control and preservation of global and local environments. However, the moss-associated microbial flora is often poorly known. Moss-associated fungi and bacteria may promote plant growth and pest control, but they may be alternative hosts for pathogens of vascular plants. In this study, the fungus Sclerotinia del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Although we did not see changes in AM fungi over time, the relative abundance of plant pathogens decreased over time (Figure 5 ), contrary to what prior research has shown in other ecosystems (Van der Putten et al, 2013 ). This an important finding as green roofs are often planted as monocultures, which can leave a plant community susceptible to pathogen accumulation (Diez et al, 2010 ; Li et al, 2014 ; Marttinen et al, 2020 ; Tamura et al, 2019 ). We examined a wide variety of roofs containing both native and nonnative species, in somewhat novel soil conditions, which may have ultimately discouraged the survival of plant‐specific pathogens and prevented the buildup of plant pathogens over time.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not see changes in AM fungi over time, the relative abundance of plant pathogens decreased over time (Figure 5 ), contrary to what prior research has shown in other ecosystems (Van der Putten et al, 2013 ). This an important finding as green roofs are often planted as monocultures, which can leave a plant community susceptible to pathogen accumulation (Diez et al, 2010 ; Li et al, 2014 ; Marttinen et al, 2020 ; Tamura et al, 2019 ). We examined a wide variety of roofs containing both native and nonnative species, in somewhat novel soil conditions, which may have ultimately discouraged the survival of plant‐specific pathogens and prevented the buildup of plant pathogens over time.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that such algal mass developments have unrecognized, detrimental effects on bryophytes, similar to those of well-known fungal infections (Fenton, 1983;Davey & Currah, 2006;Tamura et al, 2019;Rosa et al, 2020).…”
Section: Serritaenia Species With Pigmented Mucilage Colonize Various Terrestrial Substratesmentioning
confidence: 99%